Perancangan City Hotel Bintang Empat dengan Penerapan Arsitektur Eco Tech dalam Pemanfaatan Panel Surya - Lase, Robert Susanto; Rilatupa, James; Ismanto, Riyadi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The design of the Four Star City Hotel in Tebet, South Jakarta, which will implement eco-tech architecture as an innovative solution in responding to sustainability challenges in the urban hotel sector. This approach integrates modern technology with environmentally friendly principles by utilizing solar panel energy as an energy source. The hotel design is designed to optimize energy efficiency, minimize environmental impact and create maximum comfort for visitors. Apart from considering functional and aesthetic aspects, this design is oriented towards sustainable development which supports reducing the carbon footprint. The results are expected to make a positive contribution to the creation of a greener and more energy efficient urban environment.